Retinal Ganglion Cell Atrophy in Homonymous Hemianopia due to Acquired Occipital Lesions Observed Using Cirrus High-Definition-OCT - Tsutomu Yamashita; Atsushi Miki; Katsutoshi Goto; Syunsuke Araki; Go Takizawa; Yoshiaki Ieki; Junichi Kiryu; Akio Tabuchi; Yasuyuki Iguchi; Kazumi Kimura; Yoshiki Yagita (Journal of Ophthalmology)
Purpose. To report a reduction in macular ganglion cell layer and inner plexiform layer (GCL+IPL) thickness and circumpapillary retinal nerve fiber layer (cpRNFL) thickness using spectral-domain optical coherence tomography in patients with homonymous hemianopia due to posterior cerebral artery (PCA) stroke. Methods. Seven patients with PCA stroke were examined using Cirrus high-definition-OCT. The GCL+IPL thicknesses were divided into the hemianopic and unaffected sides. The relationship between the time after stroke and the GCL+IPL thicknesses in the hemianopic side was evaluated. Results. The average thicknesses of the GCL+IPL were 64.6 and 82.0 μm on the hemianopic and unaffected sides, respectively, and the measurement was significantly thinner on the former side (p=0.018). A regression analysis revealed a negative linear relationship (R2=0.574, p=0.049) between the time after stoke and the GCL+IPL thicknesses on the hemianopic side. The supratemporal and inferotemporal cpRNFL thicknesses in the eyes ipsilateral to the stroke showed a significant reduction. Conclusion. Our findings confirmed our previous observations that the degeneration of retinal ganglion cells can occur after PCA stroke. GCL+IPL thinning was demonstrated in the hemiretinae corresponding to the affected hemifields. Also, it is suggested that the retinal changes observed are progressive.